The great shark escape - Johnston, Jennifer; Enik, Ted (New York : Scholastic Inc., 2001)
On a field trip to an aquarium with Miss Frizzle and her science class, Arnold not only overcomes his fear of sea animals but also becomes the hero of the day.
K
"Based on the Magic School Bus books written by Joanna Cole and illustrated by Bruce Degen"--T.p. verso.
b
b
Keywords: Sharks -- Juvenile literature; Sharks -- Fiction; Aquariums -- Fiction; Fear -- Fiction; Heroes -- Fiction